Hubungan Antara Aspek Kognitif Sikap Dengan Partisipasi Petani Dalam Pengembangan Kopi Robusta Temanggung Berbasis Indikasi Geografis (IG)(Studi Kasus MPIG-KRT) - Saputra, Natan Rio; Lestari, Eny; Widiyanto, Widiyanto (Universitas Muhammadiyah Semarang, 2023)
Robusta coffee is one of the global agricultural product issues that has developed rapidly. Robusta coffee production has increased in various coffee-producing countries, as well as creating competition among robusta coffee-producing countries. This has an impact on coffee development efforts undertaken. One of the efforts to develop robusta coffee is through Geographical Indications (GI). The existence of Geographical Indications (GI) raises various responses from farmers, including attitude and participation. Attitude and participation are indicators of success in regional commodity development. This study aims to analyze the attitude of farmers in development geographical indication (GI) based on Temanggung robusta coffee;analyze farmer participation in development geographical indication (GI) based on Temanggung robusta coffee;analyze the relationship between attitudes and farmer participation in development Temanggung Robusta Coffee based on Geographical Indication (IG). The basic method used is descriptive quantitative with survey techniques. The results showed 1) cognitive attitudes were in the good category. 2) farmer participation is in the medium and low categories. 3) there is a significant relationship between cognitive aspects and farmer participation